Waiting area & information (Seoul, Korea Archiworld Co., Ltd, 2010)
As lifestyle of modern people changes in fast beat, increasing number of researches are conducted on various concentrations, such as function, efficiency and aesthetics of architectural and interior space. Amongst the subjects of academic attention, stands out the analysis approach, based on spatial division and type. This series provides an overview of a particular space and serves as a practical reference not only to the professionals but also to the general public
The book written with English and Korean languages
1
Keywords: Architecture -- Korea; Furniture design; Interior decoration